Search for the Exotic Decay of the Higgs Boson into a Pair of Light (Pseudo-)Scalar Higgs Boson in e+e− Collider - Nee Cheng-Hsu; Mohammadi Abdollah; Dasu Sridhara (EPJ Web of Conferences)
This study focuses on the exotic decay of the Higgs boson into a pair of light (pseudo-)scalar bosons (h → aa), where the mass of a boson ranges from 10 to 60 GeV. The primary objective is to assess the sensitivity of e+e− collider in probing these decays, particularly in the h → aa → bbττ channel. Advanced event generation and reconstruction techniques were employed, including tailored tau identification and a specialized b-jet identification method, to efficiently isolate signal from background events. The analysis approach allows for reconstruction of the a bosons from both the ττ and bb final states. The model-independent analysis resulted in a 95% confidence level upper limit on the cross-section σ (e+e− → Zh → Zaa → llbbττ) and on the branching ratio BR (h → aa → bbττ). Additionally, a model-dependent analysis can be used to set a 95% confidence level upper limit on BR(h → aa) within the two-Higgs-doublet-plus-singlet (2HDM+S) models. Both analyses show sensitivity comparable to the CMS results, with improved sensitivity in the lower a boson mass region, despite utilizing only the Z → e+e−/µ+µ− and h → aa → bbττ channels. In conclusion, the presented study demonstrates the strong potential of e+e− colliders in detecting light (pseudo-)scalar bosons, with future improvements possible through the inclusion of additional decay channels. The analysis suggests that e+e− collider has the potential to achieve greater sensitivity than LHC / HL-LHC.